2022
DOI: 10.1155/2022/5745499
|View full text |Cite|
|
Sign up to set email alerts
|

A Hybrid Model for Assessing the Performance of Medical Tourism: Integration of Bayesian BWM and Grey PROMETHEE-AL

Abstract: Medical tourism (MT) is the activity of traveling domestically or abroad to receive medical services. The scope of medical treatments covers dentistry, surgery, antiaging procedures, preventive medicine, and even some health-related treatments (meditation, physiotherapy, psychotherapy, addiction treatment, psychiatry, etc.). Due to the global boom in MT, governments are actively promoting MT packages to capture this huge business opportunity. However, what are the key factors that make MT development successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…According to some researchers, although MCDM methods provide objective and qualitative data, when the number of pairwise comparisons used in these methods is high, the accuracy rate of the research decreases and causes a waste of time (Asadpourian et al, 2020; Demir et al, 2016; Kumar et al, 2020). The fact that the BWM method, which is a new MCDM method, requires less comparison and obtains more consistent and reliable results is emphasized in many studies (Gupta & Barua, 2018; Rezaei, 2015; Stević et al, 2017; Tajer & Demir, 2022; Yang et al, 2020, 2022). However, only one study was found in which ecotourism was determined using the BWM method in protected areas (Tajer & Demir, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to some researchers, although MCDM methods provide objective and qualitative data, when the number of pairwise comparisons used in these methods is high, the accuracy rate of the research decreases and causes a waste of time (Asadpourian et al, 2020; Demir et al, 2016; Kumar et al, 2020). The fact that the BWM method, which is a new MCDM method, requires less comparison and obtains more consistent and reliable results is emphasized in many studies (Gupta & Barua, 2018; Rezaei, 2015; Stević et al, 2017; Tajer & Demir, 2022; Yang et al, 2020, 2022). However, only one study was found in which ecotourism was determined using the BWM method in protected areas (Tajer & Demir, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The high number of comparisons in this pairwise comparison method leads to a decrease in the accuracy of the research and a waste of time (Jabrayilov, 2022;Xiao et al, 2022). For this reason, many studies emphasized that the BWM method, as another current MCDM method compared to AHP, requires less comparison and can obtain more consistent and reliable results (Gupta & Barua, 2018;Rezaei, 2015;Stevi c et al, 2017;Tajer & Demir, 2022;Yang et al, 2020Yang et al, , 2022. However, no research was found in which the BWM method and/or hybrid MCDM methods were used in protected areas and within the scope of ecotourism branding.…”
Section: Research Gapmentioning
confidence: 99%
“…Moreover, the combination of Bayesian BWM and grey Preference Ranking Organization Method for Enrichment Evaluations based on Aspiration Level (grey PROMETHEE-AL) models has been applied in medical tourism, bringing high economic value for businesses. A set of four key factors and nineteen sub-criteria was constructed to estimate the performance and feasibility of medical tourism operators [33].…”
Section: Best-worst Methods Applicationmentioning
confidence: 99%
“…PROMETHEE has been successfully used in a number of interesting applications, including the selection of airport location [39,40], nature-based tourism [41,42], tourism competitiveness [43][44][45][46], supplier selection [47][48][49], medical tourism [36,50], transportation planning [51][52][53], renewable energy sources [54][55][56], aerospace industry [57][58][59], logistics [60][61][62][63], equipment selection [64][65][66][67], nanotechnology [68][69][70], medicine [71][72][73], and maritime transport [74][75][76][77], among other issues.…”
Section: Promethee-gaia Approachmentioning
confidence: 99%